Talent management versus strategic human resources management a case of evolution or revolution? - Harry, Jaqueline (University of Cape Town, 2014)
Includes abstract. === Includes bibliographical references. === The objective is to investigate the theoretical and practical differences between Talent Management and Strategic Human Resource Management and whether Talent Management in is in fact any different to Strategic Human Resource Management. Qualitative research was utilised to explore Talent Management and Strategic Human Resources Management practises in industry through the experiences and opinions of expert Executive Talent Managers. In-depth face to face interviews and a semi-structured interview was utilised to obtain specific information about the perspective, views and social contexts of the research participants. The data was subjected to qualitative content analysis in order to make valid inferences from texts to the contexts of their use.